Informacja w systemie e-administracji samorządowej - Laskowski, Piotr (Data in the System of Council e-Administration, 2007)
Considerations presented in the article confirm that a well functioning town council, as an institution, ought to be equipped with lots of various tools to support citizens activities and satisfy their needs as well. Data, as an important impulse for innovations in the management processes in the council sector, (data become information, information becomes knowledge, correctly applied knowledge becomes intelligence of an organization) have been spotted by council units managers who gradually implement so called E-administration. The efficient council e-administration may crucially increase citizens' trust in the local authorities. Furthermore, it can prevent many crisis situations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 644-654